KEBIJAKAN OTONOMI DAERAH DALAM PERTANIAN DI BALI - Harjo Suharwanto, Oliver Ottli; Sudibya, Komang Pradnyana (Kertha Negara : Journal Ilmu Hukum; Vol 11 No 9 (2023), 2024)
The autonomy legislation of the region in terms of its administrative organization is inseparable from the application of the principle of separation of powers and of inequality. Zonin might be related to the geographical place and potential of each area that can't be compared anywhere else. practice the precept of neighborhood autonomy to hold the Republic of Indonesia among the critical government and the nearby government. The question, consequently, is how applying the precept of regional cooperation can improve the welfare and internationality of areas with potentially incomparable situations such as geography and assets. nearby autonomy as a device for attaining prosperity in a really perfect shape of cooperation.